Processing of PVDF-based electroactive/ferroelectric films: importance of PMMA and cooling rate from the melt state on the crystallization of PVDF beta-crystals. Issue 22 (22nd May 2018) - De Neef, Alexandre; Samuel, Cédric; Stoclet, Grégory; Rguiti, Mohamed; Courtois, Christian; Dubois, Philippe; Soulestin, Jérémie; Raquez, Jean-Marie
Abstract : Low amounts of PMMA induce the polar crystalline phase of PVDF in a melt-state extrusion–calendering process and enhance the ferroelectric properties. Abstract : Poly(vinylidene difluoride) (PVDF) displays attractive ferroelectric/piezoelectric properties and its polar β-crystals are specifically targeted for achieving electroactive applications. However, their direct crystallization from the melt state represents a challenging task that has never been addressed using melt-state processes. The use of poly(methyl methacrylate) (PMMA) is herein investigated to promote the PVDF polar β-phase using melt-blending and extrusion–calendering technologies. The presence of the β-phase is here confirmed by ATR-FTIR and WAXS experiments with blends at a PMMA content as low as 5 wt%. The key role of PMMA for the β-phase crystallization from the melt state was unambiguously highlighted with the help of Flash DSC experiments in non-isothermal cooling mode from the melt state. PMMA is able to efficiently shift the α-to-β crystal transition to lower cooling rates (>100–200 °C s −1 ), making the achievement of the PVDF polar β-phase for these blends compatible with conventional processing tools. A crystal phase diagram is proposed for the PVDF/PMMA blends to highlight the dual effects of both PMMA and cooling rate on the PVDF crystallization during melt-processing. Ferroelectric properties were even observed for the blends containing PMMA up to 10 wt% with the highest remanent polarization obtained at 5 wt% PMMA. After 10 wt% PMMA, a progressive transition from ferroelectric to pseudo-linear dielectric behavior is observed more likely due to the presence of PMMA in the interlamellar amorphous phase of the polar PVDF spherulites as shown by SAXS experiments. In this work, we successfully demonstrated that PMMA plays a key role in the crystallization of PVDF polar crystals from the melt state, enabling large-scale and continuous extrusion processing of PVDF-based materials with attractive dielectric properties for sensing and harvesting applications.